(3aUhd bUGQ ef GdcdGe GdHdjZs - (3Ydj Hf CHj WGdH,J (B40 (3g` s
(3ChdgG (B:s
(3EjeGf GdeQA ojYQa HCjeGfg CNhc ef hGSGc aj GdTOI s
(3BNQgG (B:s
(3ef MQa GdjGA(B: (3jfcTa fhQ GdOjf EPG Yde ef dG hQY dg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3eQJHI Ydi MQha GdYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(328 (3b(B/4) s
Keywords: (3GdCOHs